You're So Amazing! - Catchpole, James ([Place of publication not identified] : Little, Brown Books for Young Readers, 2024)
"One-legged Joe is 'amazing'. He knows this because wherever he goes people always tell him he's amazing. Amazing for sliding down the slide, for kicking a ball, even walking to get an ice cream, or even just eating an ice cream. Of course, being Amazing Joe is better than being Poor Joe. But Joe doesn't want to be Amazing Joe or Poor Joe. He's happiest when he's just Joe."Publisher's description.
new kids book 2024 spring.
Keywords: Children with disabilities; People with disabilities; Emotions and Feelings; Friendship